Drug Repurposing Option for COVID-19 with Structural Bioinformatics of Chemical Interactions Approach - Parikesit, Arli Aditya; Nurdiansyah, Rizky (Cermin Dunia Kedokteran, 2020)
The SARS-CoV-2 virus is the pathogenic agent that caused the COVID-19 disease. The epicenter of this disease is the city of Wuhan, China. It is already categorized as â€œpandemicâ€ by WHO, as many countries already affected with the infections, including recently Indonesia. Although the standard RT-PCR and DNA sequencing protocols has already developed for diagnostic, no drugs are available to cure this disease until today. The anti-malaria drug of chloroquine phosphate was repurposed, as well as other anti-viral drugs. In this regard, a structural bioinformatics pipeline was utilized to validate the claim in the computational realm. Within the sphere of the online molecular docking method, it was found that all the tested repurposed drugs attached accordingly with the SARS-CoV-2 protease enzyme that plays a role in viral replication. The repurposed drugs could be proposed as drug candidates for COVID-19, after clinical trials or further laboratory testing.Virus SARS-CoV-2 adalah patogen penyebab penyakit COVID-19. Episentrum penyakit ini adalah kota Wuhan, Tiongkok. WHO mengeluarkan peringatan â€˜pandemiâ€™ karena banyak negara sudah terkena infeksi, termasuk Indonesia. Meskipun protokol RT-PCR dan sekuensing DNA standar telah dikembangkan untuk tujuan diagnostik, hingga saat ini tidak ada obat untuk menyembuhkan penyakit ini. Obat anti-malaria chloroquine phosphate dicoba, bersama dengan beberapa obat anti-virus. Alur analisis bioinformatika struktural digunakan untuk validasi di ranah komputasi. Dalam lingkup metode molecular docking secara daring, ditemukan bahwa obat tersebut tertambat dengan enzim protease SARS-CoV-2 yang berperan dalam replikasi virus. Obat ini dapat diusulkan sebagai kandidat obat untuk COVID-19, setelah pengujian laboratorium dan uji klinis lebih lanjut.